Stavovi studenata zdravstvene njege o ulozi medicinske sestre u zdravstvenom timu - Despotovic, Mile Lj (PONS - medicinski časopis, 2018)
Uvod: Javna slika sestrinstva pojavljuje se kao pozitivan, ali i kao negativan aspekt. Temelji se na mitovima, zabludama i sterotipu, što može uticati na odabir sestrinstva kao profesije, na zapošljavanje medicinskih sestara, ali i na sam rad medicinskih sestara. Cilj ovog rada je bio istražiti kakvi su stavovi i mišljenja studenata zdravstvene njege o identitetu i respektabilnosti profesije, ulozi u zdravstvenom timu, mogućnosti napuštanja države i zadovoljstvom pozicije sestrinstva u Bosni i Herecegovini. Metode: Istraživanje je bilo dizajnirano po tipu studije poprečnog presjeka. Epidemiološka anketa je sprovedena na Medicinkom fakultetu u Foči u periodu od 1. do 31. maja 2017. godine. Istraživanje je obuhvatilo 60 studenata zdravstvene njege od prve do četvrte godine studija, različitog pola i starosne dobi od 19 do 24 godina, koji su u trenutku ispitivanja pohađali studije. Rezultati. Većina ispitanih, njih 90%, je ženskog spola, dok je u istraživanju učestvovalo samo 10% muških studenata. Od ukupnog broja ispitanih studenata zdravstvene njege 43.4% se uopšte ili uglavnom ne slaže sa tvrdnjom da drugi članovi tima cijene medicinske sestre. Najveći procenat ispitanika (93,4%) se slaže sa tvrdnjom da je kontinuirano usavršavanje potrebno. Devedeset posto ispitanika se slaže sa tvrdnjom da je posao medicinske sestre jednako odgovoran kao i ostalih članova zdravstvenog tima. Kada je u pitanju zelja za odlaskom u inostranstvo, većina ( 86,6%), bih rado otišla u inostranstvo. Zaključak. Na osnovu rezultata istraživanja možemo zaključiti da među studentima prevladava nezadovoljstvo polažajem medicinske sestre u zdravstvenom timu i državi, kao i velika zainteresovanost za odlazak u inostranstvo. Ključne riječi: Medicinska sestra, uloga, edukacija, položaj, inostranstvo. ABSTRACT Introduction: The public image of nursing appears as a positive as well as negative aspects. It is based on myths, misconceptions and stereotypes, which may influence the choice of nursing as a profession, the employment of nurses, but also on the work of nurses. The aim of this study was to explore what are the attitudes and opinions of students about health care identity and respectability of the profession, the role of the health care team, able to leave the country and satisfaction of nursing positions in Bosnia and Herzegovina. Methods: The study was designed to the type of cross-sectional study. An epidemiological survey was conducted at the Medical Faculty in Foca during the period 1 to 31 May 2017. The study included 60 students of nursing from first to fourth year students of different sex and age from 19 to 24 years, who attended at the time of examination of the study. Results. Most respondents, 90% are women, while in the study involved only 10% of male students. Of the total number students of nursing 43.4% are not at all or mostly agree with the statement that other members of the team prices nurses. The highest percentage of subjects (93.4%) agree with the statement that the continuous improvement required. Ninety percent of respondents agree with the statement that the work of nurses just as responsible as the other members of the healthcare team. When it comes to the desire to go abroad, the majority (86.6%), would love to go abroad. Conclusion. Based on the survey results we can conclude that the prevailing discontent among students-position of nurses in the health care team and the country as well as the great interest in going abroad. Keywords: nurse, role, education, position, abroad.